2019 Winter Simulation Conference (WSC) 2019
DOI: 10.1109/wsc40007.2019.9004749
|View full text |Cite
|
Sign up to set email alerts
|

Application of Discrete-Event Simulation for Planning and Operations Issues in Mental Healthcare

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In terms of advancing the academic literature, at a practical level, this is one of few studies to model a system of mental health services [17] , and the first known attempt to do so in light of COVID-19. It is also one of relatively few studies to consider discrete time over discrete event simulation, addressing what is perhaps an undue balance given the computational efficiency advantages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of advancing the academic literature, at a practical level, this is one of few studies to model a system of mental health services [17] , and the first known attempt to do so in light of COVID-19. It is also one of relatively few studies to consider discrete time over discrete event simulation, addressing what is perhaps an undue balance given the computational efficiency advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Turning to the pre COVID-19 literature, it is fairly well recognised that the modelling of mental health services has been under-used when compared to aspects of physical healthcare [16] , [17] . In two case studies, Smith et al.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, it has been noted that there is a scarcity of literature reviews of the applications of simulation modelling to mental healthcare and services, as evidenced by Long and Meadows (2018) [7]. In turn, this holds true for DES as well, and Noorain et al (2019) [8] found just ten applications of DES to mental health services over the period from 2000 to 2019.…”
Section: Relevant Workmentioning
confidence: 99%
“…(2019) [8], giving a total of nineteen applications of DES to mental health services. These papers overwhelmingly focus on applications in hospital or inpatient settings, with a noticeable gap of applications to single psychology clinics, which this paper aims to add to.…”
Section: Relevant Workmentioning
confidence: 99%
“…In contrast, the mental/psychological care services have been noted as an area of neglect in OR (Bradley et al, 2017 ). For instance, existing reviews explore the application of specific OR methodologies, such as simulation (Langellier et al, 2019 ; Long & Meadows, 2018 ; Noorain et al, 2019 ), and Data Envelopment Analysis (García-Alonso et al, 2019 ), on mental healthcare services. In contrast, a comprehensive review of the application of optimisation methodologies to mental healthcare in the OR literature is lacking.…”
Section: Introductionmentioning
confidence: 99%